The UO2 2+ Complexes with 2′',2â´-(2,6-PyridindiyIdiethylidine)Dioxamohydrazide (H2dapsox) - Ivanovic-Burmazovic, Ivana; Sumar, Maja; Brčeski, I.; Hodzic, Ismet; Andjelkovic, K. (Trans Tech Publications, 2000)
A [UOclapsox] HO (fydapsox = 2′,2‴-(2,6-pyridindiyldiethyIidine)dioxamohydrazide) has been synthesized and determined by the elemental analysis, the H and C NMR spectra, IC and the electronic absorption spectra, as well as by thermal analysis (DSC and TG). The [UOzdapsox] SFhO complex's geometry is a pentagonal pyramid with two oxo oxygen atoms in apical positions and a planar pentadentate in the equatorial plane. This geometry (existing in spite of the solvents present within the crystal lattice) is resulting from the steric effects imposed by the coordinated acylhydrazone. © 2000 Trans Tech Publications,.